Amiodarone versus beta-blockers for the prevention of postoperative atrial fibrillation after cardiac surgery: An updated systematic review and meta-analysis of randomised controlled trials - Ardaya, Radhyaksa; Pratita, Jenni; Juliafina, Nusaibah Nadia; Rahman, Farhan Haidar Fazlur; Leonardo, Kevin (Europe PMC, 2022)
Background: Amiodarone and beta-blockers are widely used as prophylaxis for postoperative atrial fibrillation (AF). The current recommendations from society guidelines are inconclusive, leading to differing practices among physicians. This meta-analysis aimed to compare the efficacy of both agents in preventing postoperative AF after cardiac surgery. Methods: : We explored online medical databases, such as CINAHL, CENTRAL, MEDLINE, and EMBASE for randomised controlled trials (RCTs) comparing amiodarone and beta-blocker for prevention of AF after cardiac surgery. Outcomes analysed in this study were AF number of events and duration, hospital stay, and mean ventricular rate. Heterogeneity was assessed using the I² test, and publication bias was analysed using Egger’s test. Results: : In total, eight RCTs comprising 1370 patients met the inclusion criteria. Pooled analysis showed that patients in both groups had no significant difference in both AF episodes (RR 0.83, 95% CI 0.66 to 1.04, p=0.10) and AF duration (SMD 0.46, 95% CI -1.14 to 2.05, p=0.57). Furthermore, secondary outcome analysis on mean ventricular rate and mean hospital length of stay in both groups showed no significant difference (MD -4.48, 95% CI -14.36 to 5.39, p=0.37 and MD 0.29, 95% CI -0.06 to 0.63, p=0.11, respectively). Conclusions: : Amiodarone and beta-blockers are equally effective in preventing postoperative atrial fibrillation after cardiac surgery, with no difference in AF episode and duration, mean ventricular rate, and hospital length of stay.